Carcinoma Middle Ear with Facial Nerve Palsy and Temporal Lobe Abscess - Chowdhury, M Alamgir; Rabbani, SM Golam; Asaduzzaman, Md.; Malakar, Mousumi (Anwer Khan Modern Medical College Journal, 2013)
Carcinoma of middle ear is very rare condition being one in 20,000 new patients. The commonest primary middle ear malignancy is usually squamous cell carcinoma. A 36-year-male presented with right sided severe earache with blood stained aural discharge, associated with headache and deviation of angle of the mouth to the opposite side. He had ear discharge since childhood. On examination he had bleeding polypoidal mass in the right external auditory canal & tympanic membrane was not visualized. He also had features of facial nerve palsy. CT scan of brain finding was chronic right mastoiditis & right temporal lobe abscess causing significant mass effect. The patient was undergone Burr-hole operation. After 2 weeks right radical mastoidectomy was done. There was huge granulation tissue involving middle ear, attic & mastoid antrum and ossicles was eroded. Histopathology report revealed infiltrating squamous cell carcinoma grade-I. The patient was sent for radiotherapy & asked for follow up monthly. In long standing chronic suppurative otitis media with blood stained discharge & facial nerve palsy, middle ear malignancy should be suspected. Anwer Khan Modern Medical College Journal Vol. 4, No. 2: July 2013, Pages 49-51 DOI: http://dx.doi.org/10.3329/akmmcj.v4i2.16943